Respuestas

¡La mejor respuesta!
2013-07-22T22:23:28+02:00
7 x - 8 x + 4 + 7 = - 2 + 4 x + 3
- x + 11 = 4 x + 1
11 - 1 = 4 x + x
10 = 5 x
x = 10/5
x = 2
2013-07-22T22:54:08+02:00
7X-4.(2X-1)+7=-2.(1-2x)+3
    7X-8x-4+7= -2-4x+3
              - 5x= -10
                  x=2
verificacion= 7*2-4*(2*2-1)+7=-2*(1-2*2)+3
                         14-16+4+7= 2-8+3
                                       9=9
ok, espero q te sea lo q pedis.....................

Estoy muy agradecido de la molestia que te tomaste...